Hubungan Kepadatan Hunian dengan Skabies di Pesantren Da’rul Qur’an Kabupaten Kuningan Periode Tahun 2022 - 2023 - Duratunnisa Salsabila; Arief Budi Yulianti; Retno Ekowati (UNISBA Press, 2024)
Abstract. Scabies is an infectious skin disease caused by parasitic mites. Residential density is an important factor in increasing the incidence of scabies. Occupancy density in Islamic boarding schools can be reflected in the density of bedroom occupancy. This study aims to determine the relationship between the number of room occupants and the incidence of scabies among students at the Da'rul Qur'an Islamic boarding school, Kuningan Regency. This research is a quantitative observational study with a cross sectional approach. Respondents in the research were middle school and high school students at the Da'rul Qur'an Islamic Boarding School, Kuningan Regency, academic year 2022 to 2023. The sample size was calculated using the hypothesis test formula of different proportions and obtained 137 samples which were then randomized using a simple random sampling approach. Data was collected through distributing questionnaires which had been tested for validity using the Pearson correlation test. The collected data was then analyzed using the bivariate test (Chi Square). The research results showed that the largest age group was 14 years old (28.8%) and the largest class group came from class 3 of junior high school (37.2%). More than half of the total respondents were female (57.7%). Most respondents experienced scabies (70.8%) with more than half of the total respondents having rooms where the number of occupants did not meet the standards, namely more than 5 people per room (53.3%). The incidence of scabies in respondents whose rooms meet standards is smaller than in respondents whose rooms do not meet standards. This shows that there is a significant relationship between the number of room occupants and the incidence of scabies among students at the Da'rul Qur'an Islamic Boarding School, Kuningan Regency (p= 0.045; OR 1.710 95% CI (0.801 – 2.615)). Abstrak. Skabies merupakan penyakit kulit menular yang disebabkan oleh tungau parasit. Kepadatan hunian merupakan faktor penting dalam meningkatkan angka kejadian skabies. Kepadatan hunian di pesantren dapat tercermin dari kepadatan hunian ruang tidur. Penelitian ini bertujuan untuk mengetahui hubungan jumlah penghuni kamar terhadap kejadian skabies pada siswa pesantren Da’rul Qur’an Kabupaten Kuningan. Penelitian ini adalah penelitian kuantitatif observasional dengan pendekatan cross sectional. Responden dalam penelitian merupakan santri SMP dan SMA di Pondok Pesantren Da’rul Qur’an Kabupaten Kuningan tahun ajaran 2022 hingga 2023. Besar sampel dihitung menggunakan rumus uji hipotesis beda proporsi dan diperoleh 137 sampel yang kemudian diacak dengan pendekatan simple random sampling. Data dikumpulkan melalui pembagian kuesioner yang telah diuji validitas menggunakan uji korelasi pearson. Data yang terkumpul kemudian dianalisis menggunakan uji bivariate (Chi Square). Hasil penelitian menunjukkan bahwa kelompok usia paling banyak yaitu berusia 14 tahun (28,8%) dan kelompok kelas paling banyak berasal dari kelas 3 SMP (37,2%). Lebih dari setengah total responden berjenis kelamin perempuan (57,7%). Sebagian besar responden mengalami skabies (70,8%) dengan lebih dari setengah total responden memiliki kamar dengan jumlah penghuni kamar tidak memenuhi standar yaitu lebih dari 5 orang per kamar (53,3%). Kejadian skabies pada responden dengan penghuni kamar sesuai standar lebih kecil dibandingkan responden dengan penghuni kamar tidak sesuai standar. Hal ini menujukkan adanya hubungan yang signifikan antara jumlah penghuni kamar dengan kejadian skabies pada santri di Pondok Pesantren Da’rul Qur’an Kabupaten Kuningan (p= 0,045; OR 1,710 95% CI (0,801 – 2,615)).